Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Gravestones for Diana Faye Slaughter (12/15/1966-12/15/1966) and Dale Richard Slaughter (1/19/1947-7/7/1962)